4 - Introduction du salariat dans les modes de production au Gabon: 10.4314/ad.v25i3.22104 - Emery, Etoughé-Efé Jean (Africa Development, 2022)
The notion of salary, unknown to the traditional Gabonese production systems that were based on a system of community work and on social equilibrium, has been introduced by colonisation. Although the rhythm of work in traditional society is very intense, it is not functioning in terms of clock time, rather in terms of biological clock. That is the reason why the indigenes are accused of laziness.The advent of hard labour has been motivated by colonisers' will to compel the Negro to execute community work for Europe. In 1903, the payment of salary has been regulated through a decree dated May 11, and from then on, each village's chief, on behalf of his citizens, signs a work contract. At the same time a workbook is drawn up for each employee.With these first forms of wages appear the pioneers of the working class who are evolving in the wood industry in Gabon.